State Observer-Based Output Feedback Control Applied to a Time-Discrete Coupled Inductors Cuk Converter - Quispe, Brajhan B. [UNESP]; Tisza, Juan F. [UNESP]; Alburqueque, Marlon J.; De Ribeiro, Jean Marcos [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2021)
This paper presents the design of a state observer-based output feedback controller applied to a discrete-time coupled inductors Cuk converter. The anti-windup concept is employed in the design of the final controller in order to guarantee an adequate dynamic performance against the saturation effect at the control input. Finally, simulation results are presented in order to validate the effectiveness of the proposed control system.
Keywords: Anti-windup; Bidirectional Cuk Converter; Discrete System; State Observer